Granulation Tissue Eroding the Subchondral Bone Also Promotes New Bone Formation in Ankylosing Spondylitis. Issue 10 (28th September 2016) - Bleil, Janine; Maier, Rene; Hempfing, Axel; Sieper, Joachim; Appel, Heiner; Syrbe, Uta
Abstract : Objective: We previously suggested that fibroblast‐rich granulation tissue eroding the subchondral bone is instrumental in the joint remodeling that occurs in ankylosing spondylitis (AS). The purpose of this study was to determine if this granulation tissue also carries bone‐forming capabilities, which we approached by searching for bone‐forming cells (hypertrophic chondrocytes, osteoblasts) in its vicinity. We also assessed adipogenic tissue transformation, which has been suggested to be an intermediate feature in AS bone formation based on imaging studies. Methods: The facet joints of AS patients, osteoarthritis (OA) patients, and autopsy subjects (controls) were screened for subchondral granulation tissue. We searched for hypertrophic chondrocytes by assessing RUNX‐2, type X collagen, and matrix metalloproteinase 13 (MMP‐13) expression, for osteoblasts by analyzing RUNX‐2, CD56, and type I collagen expression, as well as for signs of new bone formation. Adipocytes and lipid accumulation were assessed in Safranin O–stained sections. Results: In the joints of AS and OA patients, RUNX‐2–positive cells were found to be lining the granulation tissue. These cells coexpressed type I collagen but lacked type X collagen and MMP‐13 expression, confirming their osteoblastic nature. In 91% of AS joints and in 20% of OA joints ( P  < 0.05), we observed foci of new bone formation at contact zones between the granulation tissue and the cartilage. Joints containing bony spots showed greater replacement of the adjacent bone marrow by granulation tissue than did joints without bone formation ( P  < 0.05). The granulation tissue often contained adipocytes and lipid accumulations. Replacement of the subchondral bone marrow by fat tissue was also frequently found but was not associated with new bone formation. Conclusion: The subchondral granulation tissue carries osteoblasts, which promote new bone formation, leading to intraarticular ankylosis of the facet joints in AS.